Integrated analysis of biochemical, transcriptomic, and metabolomic response mechanisms in Ussuri catfish (Pseudobagrus ussuriensis) under acute heat stress - Qing Liu; Yang Cao; Ruyi Hu; Libo Gu; Lirong Yang; Yu Liu; Weiwei Wang; Liang Xiao; Bugao Li (Ecotoxicology and Environmental Safety)
Fish metabolism, growth, development, and physiological conditions are highly sensitive to fluctuations in water temperature. The Ussuri catfish (Pseudobagrus ussuriensis) is an important native economic species in China. However, research on heat stress in P. ussuriensis, particularly concerning gene expression and metabolites, remains limited. In this study, we conducted histological observations, biochemical measurements, transcriptomic analysis, and metabolomic analysis on liver tissue from a control group (22 ℃), an acute heat stress group (34 ℃, with samples taken at 0, 3, 6, 12, and 24 h), and a recovery group (sampled 24 h after recovery to 22 ℃). Histopathological analysis showed that liver damage worsened with the duration of heat stress. Biochemical results indicated that acute heat stress significantly impacted the activities of superoxide dismutase, catalase, and alanine aminotransferase, as well as the levels of glutathione, malondialdehyde, and total antioxidant capacity, with alterations remaining even after temperature recovery. Transcriptomic and metabolomic analyses revealed that compared to the control group, 3482, 800, 980, and 1479 differentially expressed genes (DEGs) were detected at 0, 6, and 24 h of acute heat stress and at 24 h post-recovery, respectively. Similarly, 114, 151, 365, and 326 differentially expressed metabolites (DEMs), respectively, were detected at the same time points. Furthermore, when comparing 24 h of heat stress with 24 h of recovery, 1279 DEGs and 157 DEMs were identified. Functional enrichment analysis revealed that these DEGs and DEMs were significantly enriched in key pathways, such as endoplasmic reticulum protein processing and glutathione metabolism, with significant changes continuing into the recovery phase. Additionally, substantial alterations in the expression levels of amino acids, sugars, and lipids were observed during heat stress. These findings provide valuable insights into the defense mechanisms of fish under high-temperature stress and lay a theoretical foundation for breeding heat-resistant P. ussuriensis strains, as well as improving sustainable aquaculture management.